2007
DOI: 10.1017/s1355617708080090
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of risperidoneversushaloperidol on verbal memory, attention, and symptomatology in schizophrenia

Abstract: There is evidence in the literature that cognitive functions in schizophrenia (SC) may be improved by atypical neuroleptics (NLPs) in contrast to typical medication, but there is still controversy regarding this apparent superiority of atypical drugs. In this study, we assessed the differential effects of risperidone and haloperidol on verbal memory, attention, and psychiatric symptoms in SC. The performance of 28 SC participants, randomly assigned to risperidone (2-6 mg0day) or haloperidol (2-40 mg0day), was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The literature suggests that both severity of positive and negative symptoms (Hughes et al, 2003) and longer durations of untreated psychoses (Amminger et al, 2002;Lappin et al, 2007) are linked to poorer cognitive performance in first episode psychosis. Effects of antipsychotic drugs on cognitive performance in patients with schizophrenia are not entirely clear: while some studies found positive effects (Selva-Vera et al, 2010;Shim et al, 2012) others found either no effects (Remillard et al, 2008;Kelly et al, 2009) or effects varying by type of medication (conventional/atypical) (Müller et al, 2005). Fourth, the individuals in our sample were all males.…”
Section: Discussionmentioning
confidence: 78%
“…The literature suggests that both severity of positive and negative symptoms (Hughes et al, 2003) and longer durations of untreated psychoses (Amminger et al, 2002;Lappin et al, 2007) are linked to poorer cognitive performance in first episode psychosis. Effects of antipsychotic drugs on cognitive performance in patients with schizophrenia are not entirely clear: while some studies found positive effects (Selva-Vera et al, 2010;Shim et al, 2012) others found either no effects (Remillard et al, 2008;Kelly et al, 2009) or effects varying by type of medication (conventional/atypical) (Müller et al, 2005). Fourth, the individuals in our sample were all males.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore the results have to be interpreted with caution. A study comparing the effects of risperidone and haloperidol on verbal memory found that performance on a verbal memory task remained essentially unchanged in both groups (22). Since the authors did not include a non-medicated schizophrenia group but included a healthy group as control this mainly provides evidence that there is no difference between risperidone and haloperidol.…”
Section: Verbal Learning and Memorymentioning
confidence: 99%
“…The magnitude of improvement did not differ between patients treated with haloperidol and those treated with secondgeneration antipsychotics. In a long-term study over 12 months 2 Journal of Psychopharmacology 0(0) reported by Rémillard et al (2008) neither conventional nor atypical antipsychotic medications improved neurocognitive functioning significantly. Analysing the dataset from 410 participants of the Clinical Antipsychotic Trials in Intervention Effectiveness (CATIE) trial, Sakurai et al (2012) found a significant association between neurocognitive function and the estimated D 2 occupancy levels.…”
Section: Introductionmentioning
confidence: 99%